Study of urban landscapes in Azerbaijani cities - Amanova, Shahnaz Salim; Hasanaliyeva, Laman Hasan; Dadashova, Khumar Khanim (Universidad y sociedad (Cienfuegos), 2023)
ABSTRACT Data collection for smart city implementation is becoming increasingly important in today's urban environment. These cities of the future are built from the incorporation of information and communication technologies (ICT) in their infrastructures and services with the aim of improving the efficiency, sustainability and quality of life of their inhabitants. In this sense, the systematic acquisition of data is positioned as an essential practice for the successful growth of these cities with a vision of the future and is supported by a series of pillars. However, it is essential to recognize that the relevance of the information varies according to the particularities and priorities of each city, therefore a flexible and adaptive approach is required to take full advantage of the potential of smart cities. Considering this, the aim of this paper was to analyze relevant information for the future development of the concept of smart cities in Azerbaijan. The work presents the results of analyzes carried out in the cities of Ganja, Mingachevir and Yevlakh, which are important cities of the Republic of Azerbaijan. During the investigation, both traditional and modern methods were used, emphasizing the processing of satellite images. We believe that this information will be relevant for future research on the subject, and that making it more visible will favor an environment of collaboration and the gradual active involvement of the population in decision-making, thus promoting the creation of more inclusive and consistent policies, with the real needs of the inhabitants.